Valuaciones monetarias y jerarquías sociales: evidencias empíricas y desarrollos conceptuales - Wilkis, Ariel; Figueiro, Pablo J. (El Colegio de México, 2019)
Based on lines of work that support the non-neutral nature of money and deepening recent perspectives on evaluations in economic life, this article takes up empirical cases of art history, sociology and anthropology to propose an articulation between monetary valuations and the study of social hierarchies. For this, four specially selected cases are recovered to reflect on the peculiarities that the valuation processes assume in heterogeneous social and institutional contexts and how these processes are inherent to the construction, maintenance and modification of social hierarchies.